Complete stories - Parker, Dorothy 1893-1967.; Breese, Colleen (New York Penguin Books, 2003)
A complete collection of short stories by the noted humorist features Parker's best known tales, along with thirteen stories never previously collected.
Reprint. Originally published: 1995.
Keywords: United States -- Social life and customs -- 20th century -- Fiction; Fiction